2010
DOI: 10.1002/ar.21151
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Apoptosis in the Cystic Duct During Metamorphosis of a Japanese Lamprey, Lethenteron reissneri

Abstract: A nonparasitic lamprey in Japan, Lethenteron reissneri, stops feeding prior to the commencement of metamorphosis. Resumption of feeding cannot take place due to major alterations in the digestive system, including loss of the gall bladder (GB) and biliary tree in the liver. This degeneration of bile ducts is considered to depend on programmed cell death or apoptosis, but molecular evidence of apoptosis remains lacking. Using terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) staining and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…Moreover, the degeneration of bile ducts has been associated with the development of marked periductal fibrosis due to fibroblast activation caused by leaked biliary materials (Youson et al, 1987;Yamamoto et al, 1986). Our observation of apoptosis in biliary epithelial cells detected prior to changes in hepatocyte morphology (Morii et al, 2010) was consistent with the results of previous reports. Intrahepatic cholestasis may regulate the remodeling of hepatocytes by changing the way cholesterol is metabolized, the expression of transporters in the basolateral membrane and the disappearance of tight junctions in hepatocytes surrounding bile canaliculi.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, the degeneration of bile ducts has been associated with the development of marked periductal fibrosis due to fibroblast activation caused by leaked biliary materials (Youson et al, 1987;Yamamoto et al, 1986). Our observation of apoptosis in biliary epithelial cells detected prior to changes in hepatocyte morphology (Morii et al, 2010) was consistent with the results of previous reports. Intrahepatic cholestasis may regulate the remodeling of hepatocytes by changing the way cholesterol is metabolized, the expression of transporters in the basolateral membrane and the disappearance of tight junctions in hepatocytes surrounding bile canaliculi.…”
Section: Discussionsupporting
confidence: 92%
“…Chronological TUNEL analysis of metamorphosing lampreys showed that apoptosis started in the region around the CD and then progressed towards both the periphery and the center (Morii et al, 2010). Figure 8 shows that the epithelial cells of the GB were positive for TUNEL staining.…”
Section: Tunel Stainingmentioning
confidence: 98%
See 2 more Smart Citations
“…As might be expected, the degeneration of bile ducts occurs via programmed cell death or apoptosis in a related, nonparasitic lamprey, Lethenteron reissner, and in the sea lamprey, Petromyzon marinus. 14,15 Similar to the lamprey, several reports have documented cholangiocyte apoptosis as evidenced by positive transferasemediated dUTP nick end labeling (TUNEL) staining of cholangiocytes in the livers of patients with biliary atresia. Although apoptosis is a normal process in remodeling of the mammalian ductal plate during liver development, it would not be expected in the extrahepatic biliary system except as part of the process of immunologic ductal injury.…”
mentioning
confidence: 99%